Revitalizing Traditional Markets as Culinary Places: Increasing Young Generation's Shopping Interest at Sentul Market, Yogyakarta - Sabilla, Mutiara Safa; Kholid, Anwar (Universitas Medan Area, 2024)
This article aims to analyze the government's role in revitalizing the Sentul Yogyakarta market and why the younger generation is one of the factors considered in revitalizing the Sentul Yogyakarta market. Revitalizing traditional markets is one of the government's efforts to improve community welfare. In Indonesia, there has been a lot of research discussing the issue of revitalizing traditional markets, but there is still very little research that includes the perspective of the younger generation. This research uses qualitative methods, data collection is carried out by direct observation and interviews with sources, namely market traders, trade services, and visitors to the Sentul market. The findings show that the Government acts as the lead sector in coordinating every stage of revitalization starting from the design stage, socialization, temporary relocation of traders, and construction to the evaluation stage. This research also shows that the younger generation is an important consideration in the revitalization of Sentul Market. This is proven by the construction of a rooftop as a culinary center to attract the interest of the younger generation. However, due to the current lack